Invasive Cervical Root Resorption: A Comprehensive Review on Pathogenesis, Diagnosis, and Treatment - Asgary, Saeed; Dianat, Omid (Iranian Endodontic Journal, 2024)
Invasive cervical root resorption (ICRR) is a dental pathology, marked by unexpected destruction originating in the cervical region of the tooth. This comprehensive literature review provides a holistic view into the pathogenesis, clinical manifestation, and precise management of ICRR, aiming to guide endodontists and enhance patient care and treatment outcomes. The review delves into the potential etiology of ICRR, covering contributing factors such as trauma, orthodontic treatment, and other pertinent conditions. It outlines the clinical and radiographic indicators, underscoring the crucial role of early detection and precise diagnosis in effectively managing and halting ICRR progression. The exploration of treatment approaches is thorough, ranging from non-surgical methods like vital pulp therapy or root canal treatment to surgical interventions. This review accentuates the essential role of interdisciplinary collaboration among diverse dental specialties in enhancing ICRR management. It highlights the importance of a consolidated strategy in enhancing treatment outcomes and preserving tooth structure and function. Moreover, it investigates prevention methods, risk evaluation, and identifies prospective research pathways to address the existing knowledge gaps.